Fiscal reaction under endogenous structural changes in Brazil - Andrei G. Simonassi; Ronaldo A. Arraes; Augusto Marcos C. de Sena (EconomiA, 2014)
Regarding the importance of fiscal policy in smoothing the impact of shocks such as the international financial and economic crises, the paper analyzes the sustainability of the Brazilian fiscal policy by taking into consideration the possibility of multiple endogenous structural breaks on the coefficients of government reaction function. From monthly data in the period 1991–2008, tests on the reliable estimates dictate the occurrence of structural change in May 1994, and another in February 2003. There has been a situation of fiscal solvency in Brazil, but only from May 1994 the hitherto innocuous actions of government to formulate policies on public debt turn out to be significant, as it rose twofold after February 2003. This reinforces the existence of a more flexible alternative to implement strategic policy in Brazil, if an eventual alternative for increasing public spending is a way of hindering the effects of international financial crises without compromising the fiscal targets.